Facebook Commentaries in Leni Robredo’s Presidential Campaign: Sexism Illumination - Capuyan, Ailyn; Capuyan, Mark Paul; Jayme, Percky Daffodil; Minoza, Joemar; Flores, Rogela (OKARA: Jurnal Bahasa dan Sastra, 2023)
Sexism in social media sites has rarely been looked into and has been scarcely seen as a crucial subject to research studies, which is alarming to the desire to achieve an equal and just society. This study focused on the sexist rhetoric used in the commentaries on 2022 Presidentiable Leni Robredo to reveal how prevalent and existing sexism in the Philippines through language is. Comments are gathered from Facebook posts pertaining to Atty. Leni Robredo. The study employed a qualitative-descriptive research design, specifically content analysis, to analyze sexist words and phrases. The weight and capability of each word's sexism were compared when it is used to insult, degrade, and malign a woman to determine its level of sexism. The study revealed that deep-rooted gender biases and sexism through language are still highly functioning in society, as is observed and experienced online. Hostile sexism is the most pervasive level of sexism and hence contributes to widespread sexism in the country and is more commonly done by the majority of males than females. It is recommended that academe should promote unbiased gender language by making every term and phrase gender inclusive as an introduction lesson/subject) to avoid sexism.